Functional Validation of the Roles of Cytochrome P450s in Tolerance to Thiamethoxam and Imidacloprid in a Field Population of Aphis gossypii. - Lv, Y.; Wen, S.; Ding, Y.; Gao, X.; Chen, X.; Yan, K.; Yang, F.; Pan, Y.; Shang, Q. (Journal of Agricultural and Food Chemistry, 2022)
Field populations of Aphis gossypii (SDR) have evolved high resistance to neonicotinoids, including thiamethoxam and imidacloprid. Synergism bioassays and transcriptomic comparison of the SDR and susceptible (SS) strains revealed that the cytochrome P450s may contribute to the neonicotinoid resistance evolution. The transcripts of some P450s were constitutively overexpressed in the SDR strain, and many genes showed expression plasticity under insecticide exposure. Drosophila that ectopically expressed CYPC6Y9, CYP4CK1, CYP6DB1, and CYP6CZ1 showed greater resistance (>8.0-fold) to thiamethoxam, and Drosophila that expressed CYPC6Y9, CYP6CY22, CYP6CY18, and CYP6D subfamily genes showed greater resistance (>5-fold) to imidacloprid. Five P450 genes that caused thiamethoxam resistance also conferred resistance to ?-cypermethrin. Furthermore, the knockdown of CYP4CK1, CYP6CY9, CYP6CY18, CYPC6Y22, CYP6CZ1, and CYP6DB1 dramatically increased the sensitivity of the SDR strain to thiamethoxam or imidacloprid. These results indicate the involvement of multiple P450 genes, rather than one key gene, in neonicotinoid resistance in field populations.